Self-esteem and the perceived obligation to respond: effects on children's testimony - Howie, Pauline M. (Legal and criminological psychology, 1996)
Third and fourth grade children were exposed to a staged event then asked misleading and non-misleading questions about it a week later. Children were categorized as high or low in self-esteem using teacher ratings of behaviour in the school setting. Prior to questioning they were given one of two sets of instructions: one conveying a low obligation to respond with specific answers, and the other conveying a high obligation. Children with higher self-esteem showed greater resistance, less yielding and fewer 'don't know’ responses to misleading questions than children with lower self-esteem. Children in the low obligation conditions produced more ‘don't know’ responses to misleading questions than children in the high obligation conditions, but there were no differences between instruction conditions in resistance or yielding. There was no evidence that the instructions used in the present study were able to overcome the disadvantage of low self-esteem children.